Effects of Low-Dose Radon Therapy Applied Under Hyperthermic Conditions (RnHT) on Inflammatory and Non- Inflammatory Degenerative Disease Conditions - Moder, Angelika; Dobias, Heidi; Ritter, Markus (IntechOpen, 2013)
None